Աղավ անապատի 1292 թ. նկարազարդ ձեռագիրը - Բարսեղյան, Լուսինե («Նաիրի» հրատ.)
Среди многочисленных монастырей Вайоц дзора в XIII веке действовал также скрипторий пустыни Ахав, из которого до нас дошло лишь одно Евангелие (Матенадаран 6292). Рукопись скопировал, предположительно также проиллюстрировал в 1292 г. писец Матеос, известный как скульптор и архитектор княжеского рода Прошянов. Евангелие переписано на бумаге и содержит 3 листа письма Евсевия, каноны согласия (7 листов), а также 4 портрета евангелистов и титульные листы. В художественном оформлении и иконографии рукописи ярко выражены древние традиции Сюникской школы. Евангелисты изображены парами, что характерно для иконографии Иоанна, начиная с XI века часто изображаемого вместе с Прохором. Все четыре евангелиста стоя диктуют сидящим писцам. Есть византийские, сирийские, коптские, грузинские и армянские памятники, в которых Евангелистов сопровождают другие персонажи: Марка – Петр, а Луку – Павел, но не известно ни одного иного памятника, где бы все 4 евангелиста имели писцов. Следовательно, рукопись пустыни Ахав по своему художественному стилю и своеобразной иконографии – важный памятник армянского искусства миниатюры. The Aghav hermitage, which was functioning in the 13th century, was one of Vayots Dzor‟s numerous monasteries. Only one Gospel copied there in 1292 (M6292) has reached us. Its scribe Mateos, the famous sculptor and architect of the Proshean noble family, presumably also illuminated the manuscript. The codex is written on paper and contains the Letter of Eusebius (3 folios), the Canon Tables (7 folios) and the portraits of the Evangelists with title-pages. From an artistic and iconographic point of view, the manuscript reflects the old traditions of the Syunik School of miniature art. The Evangelists are depicted in pairs, which is typical of the iconography of John, as from the 11th century onwards he is often portrayed with Prochorus. All four Evangelists are standing and dictating texts to sitting scribes. There are Byzantine, Syriac, Coptic, Georgian and Armenian manuscripts in which the Evangelists are accompanied by various figures: Mark by Peter, and Luke by Paul. No other instance is known where all of the Evangelists are depicted with scribes. In this sense, the Gospel of the Aghav hermitage with its original iconography and artistic style is a valuable example of Armenian miniature art.
Keywords: Մանրանկարչություն; Ձեռագրեր